Analysis of the Absorption Capacity of Zeolite Against NI(II) and Zn(II) Metal Ions - Simbolon, Ryandi; Iis Siti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the synthesis process of zeolite X from rice husk waste using the addition of optimum materials and to apply the synthesized zeolite X as an adsorbent for Ni(II) and Zn(II) metal ions with variations in concentration and pH. The tools used include: three-neck flask, furnace, electric oven, analytical balance, beaker, stopwatch, centrifuge, pH meter, sieve, porcelain, glass beaker, dropper pipette, volume pipette, test tube, stir bar, filter paper, magnetic stirrer. The materials used include: Rice husks, Aluminum Foil waste, Sodium Hydroxide (NaOH(s)) p.a, Sodium Ethylene diamine tetra acetate (Na2EDTA(s))p.a, Aquades (H2O), Nitric acid (HNO3)p. a, Nickel (II) chloride (NiCl2), Zinc nitrate Zn(NO3)2, and Sodium hydrogen phosphate (Na2HPO4). FT-IR characterization results showed the formation of vibrations at 607.35 cm-1, indicating the formation of zeolite. XRD characterization results showed a purity level of 87.5%, which is sufficient to bind metal impurity ions. The research results indicate that the synthetic zeolite X from rice husk waste, when tested using AAS analysis, exhibits adsorption capacity for Ni(II) and Zn(II) under optimum conditions at a concentration of 150 ppm and pH 7.